1992
DOI: 10.1111/j.1467-8624.1992.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, Aptitude, and Strategic Remembering

Abstract: , 461-473. Second-and fourth-grade children were classified according to their knowledge of soccer (experts vs. novices) and IQ (high vs. low), and given 2 sort-recall tasks. One task included items related to the game of soccer and the other included items from familiar natural language categories. Previous research has shown that expertise in a snbject can compensate for low levels of performance on text comprehension tasks. Our results, the flrst examing the effects of both expertise and intelligence on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…In a recent study on the impact of domain-specific knowledge on performance in a sort-recall task (Schneider and Bjorklund, 1992), we found that soccer experts recalled more than soccer novices when the task was to remember a list of soccer-related pictures, but that intelligence had an independent effect. That is, when the task was to use organizational strategies in order to learn and remember semantically clusterable materials, the more intelligent soccer experts outperformed the less intelligent experts, and the more intelligent novices outperformed the less intelligent novices.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study on the impact of domain-specific knowledge on performance in a sort-recall task (Schneider and Bjorklund, 1992), we found that soccer experts recalled more than soccer novices when the task was to remember a list of soccer-related pictures, but that intelligence had an independent effect. That is, when the task was to use organizational strategies in order to learn and remember semantically clusterable materials, the more intelligent soccer experts outperformed the less intelligent experts, and the more intelligent novices outperformed the less intelligent novices.…”
Section: Discussionmentioning
confidence: 90%
“…Alexander et al (1994) once described the linear interest-knowledge relationship: the relationship is weak in students with low and intermediate levels of knowledge and is becoming stronger with knowledge growth and is stronger in knowledgeable students. Studies conducted on various populations and domains have confirmed this relationship (see Carnine and Carnine, 2004, Morris et al, 1985, Schneider and Bjorklund, 1992, Willingham, 2007.…”
Section: Knowledge and Interestmentioning
confidence: 83%
“…This finding is consistent with an increased elaboration of injustice and justice concepts among victim‐sensitive persons. Unjust and just information can be better encoded into an elaborate pertinent memory structure so that retrieval is facilitated (Anderson, ; Schneider & Bjorklund, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a more elaborate knowledge structure in the domain of injustice should enhance the encoding of new pertinent information so that later retrieval is facilitated (Anderson, ; Schneider & Bjorklund, ). In line with this assumption, studies have shown that persons high in justice sensitivity display more accurate memory performance for unjust but not for neutral information in newspaper articles compared with persons low in justice sensitivity (Baumert et al, ).…”
mentioning
confidence: 99%